(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
Language is one of humanity’s oldest and most essential inventions. It is the tool through which we express our thoughts, communicate with others, and share knowledge and experiences. As such, language holds a significant role in social life, personal development, and culture. The phrase “when language changes, the world changes” captures the profound impact that language evolution has on society and human lives. In this article, I will explore the social, cultural, and philosophical aspects of language change.